Ensaio não destrutivo para recuperação de numeração obliterada em armas de fogo - Batista, Rivelino Barata de Sousa (2019)
Firearms produced around the world have a unique identification engraved on its structure. That is composed of a registry of letters and / or numbers that has the function of identifying the weapon and its specific characteristics with the manufacturer, such as batch, year of manufacture, material used among others. As with the manufacturer, the serial number is the object of control of the agencies that oversee the trade and distribution of weapons in a society. In Brazil the controls are performed through two large systems: the SIGMA in operation in the Brazilian Army and the SINARM operated by the Federal Police Department. These systems use the serial number as a fundamental element in the identification of the property of the firearm, its manufacturer and specific characteristics such as gauge and dimensions. In order to facilitate clandestine trade, as well as to break the moorings that control the property of the weapons circulating in the country, criminals often obliterate the serial number contained in the body of the weapon, making it difficult to control the state and identify the perpetrators. Forensic expertise has evolved to recover the numbering removed of firearms and consequently identify the perpetrator of crimes. However, many procedures are by means of destructive tests that do not reach the objective, end up damaging the part to the point of not allowing other tests. In this work, the eddy current test combined with the optical-magnetic reading will be used to identify signatures in parts with the objective of recovering by non-destructive testing the serial numbering on weapons that have been removed, without damaging its structure.